Swine acute diarrhoea syndrome coronavirus (SADS-CoV) Nsp5 antagonizes type I interferon signaling by cleaving DCP1A - Huang, Hai-xin; Zhao, Chen-chen; Lei, Xiao-xiao; Zhang, Xin-yu; Li, Yu-ying; Lan, Tian; Zhao, Bao-peng; Lu, Jing-yi; Sun, Wen-chao; Lu, Hui-jun; Jin, Ning-yi (Frontiers in Immunology, 2023)
Swine acute diarrhoea syndrome coronavirus (SADS-CoV), which is a recently discovered enteric coronavirus, is the major aetiological agent that causes severe clinical diarrhoea and intestinal pathological damage in pigs, and it has caused significant economic losses to the swine industry. Nonstructural protein 5, also called 3C-like protease, cleaves viral polypeptides and host immune-related molecules to facilitate viral replication and immune evasion. Here, we demonstrated that SADS-CoV nsp5 significantly inhibits the Sendai virus (SEV)-induced production of IFN-β and inflammatory cytokines. SADS-CoV nsp5 targets and cleaves mRNA-decapping enzyme 1a (DCP1A) via its protease activity to inhibit the IRF3 and NF-κB signalling pathways in order to decrease IFN-β and inflammatory cytokine production. We found that the histidine 41 and cystine 144 residues of SADS-CoV nsp5 are critical for its cleavage activity. Additionally, a form of DCP1A with a mutation in the glutamine 343 residue is resistant to nsp5-mediated cleavage and has a stronger ability to inhibit SADS-CoV infection than wild-type DCP1A. In conclusion, our findings reveal that SADS-CoV nsp5 is an important interferon antagonist and enhance the understanding of immune evasion by alpha coronaviruses.